Time flies when you are having fun: The first regular 2026 issue - Thomas Gültzow; Filipa Teixeira (European Health Psychologist, 2026)
This editorial introduces the first regular issue of The European Health Psychologist in 2026. The contributions featured in this issue demonstrate how ideas originating from EHPS workshops, conference roundtables, keynote lectures, and Synergy activities continue to evolve into scholarly outputs that advance health psychology. Spanning science communication, applied health psychology, occupational well-being, and the influence of social media on research and practice, the articles showcase the breadth of the discipline and the value of continued collaboration beyond Society events. Together, they reflect the vibrant exchange of ideas, innovation, and community spirit that continue to shape health psychology and its real-world impact.